Occurrence of microplastics in the gastrointestinal tract of benthic by–catches from an eastern Mediterranean deep–sea environment. (January 2022) - Esposito, Giuseppe; Prearo, Marino; Renzi, Monia; Anselmi, Serena; Cesarani, Alberto; Barcelò, Damià; Dondo, Alessandro; Pastorino, Paolo
Abstract: Concern about microplastic pollution little is known about levels in deep-sea species; to fill this knowledge gap, levels of microplastics in the gastrointestinal (GI) tracts of 34 fish from eight different deep–sea by–catches: blackmouth catshark, lesser spotted dogfish, and velvet belly, armless snake eel, hollowsnout grenadier, phaeton dragonet, royal flagfin, and slender snipe eel were measured. All were collected at the same site (east Sardinia, Mediterranean Sea; 40°10′12.49″N, 9°44′12.31″E) using a bottom gillnet at depths between −820/250 and −1148 ft./350 m. Microplastics (MPs) were retrieved in 16 out of 34 fish. At least one microplastic item was found in 48% (33%, E. spinax - 75%, G. melastomus ) of the samples. The most frequent was polyethylene (PE), with nine items (filaments, films, fragments) found in five specimens. This preliminary study of by–catches adds new data on MPs ingestion by species inhabiting a deep–sea environment of the Mediterranean. Graphical abstract: Unlabelled Image Highlights: Microplastics (MPs) in the deep–sea environments: submarine canyons. Eight deep–sea species were collected from the Gulf of Orosei (east Sardinia, Italy) The study measured MPs levels and characteristics in deep–sea by–catches. MPs varied in shape and colors across species.